دور المجتمع المدني في تكريس الديمقراطية التشاركية في الجزائر - صبري عياري; شيماء دراوات (My University, 2025)
ABSTRACT institutions, to achieving the public good, on the one hand, and embodies participatory democracy, on the other, is the result of a combination of political, economic, and social factors. Civil society organizations in developed countries play a significant role in achieving development and embodying effective citizen participation in achieving participatory democracy through civil society. Today, civil society organizations have become an effective body alongside the public authority in strengthening the role of civil society in providing services that the state has been unable to meet. They also play a vital role in monitoring government performance and offering alternatives that reflect citizens' needs and aspirations through participatory democracy. In Algeria, civil society has developed in a similar way to other countries around the world, especially during the last three decades, specifically after the issuance of the 1989 Pluralist Constitution, which established political and economic openness to the world by establishing, organizing, and involving civil society institutions within a participatory democratic framework, through an arsenal of legislation and laws. This has become a driving force for social and economic change and local and national development through partnership in political life, as it participates effectively in community initiatives through participatory democracy, which enhances cooperation between it and the state to achieve stability, progress, and local development within a participatory democratic framework by activating the role of civil society and attempting to overcome various obstacles and challenges in order to establish participatory democracy. .................................. ملخص إن الحاجة إلى وجود مجتمع مدني فعال يساهم إلى جانب مؤسسات الدولة في تحقيق الصالح العام من جهة، ويجسد الديمقراطية التشاركية من جهة أخرى نتيجة اجتماع مجموعة من العوامل السياسية والاقتصادية والاجتماعية، حيث تمارس تنظيمات المجتمع المدني في الدول المتطورة دورا مهما في تحقيق التنمية وتجسيد مشاركة المواطن الفعالة في تحقيق الديمقراطية التشاركية عبر المجتمع المدني، حيث أصبحت اليوم منظمات المجتمع المدني هيئة فاعلة الى جانب السلطة العامة في تعزيز دور المجتمع المدني في تقديم الخدمات التي عجزت الدولة عن تلبيتها، كما تلعب دورا حيويا في مراقبة أداء الحكومي وتقديم بدائل تعكس احتياجات المواطنين وتطلعاتهم من خلال الديمقراطية التشاركية. في الجزائر تطور المجتمع المدني على غرار بقية دول العالم خاصة خلال العقود الثلاثة الأخيرة وبالتحديد بعد صدور دستور التعددية 1989 الذي اسس للانفتاح السياسي والاقتصادي على العالم من خلال التأسيس لأنشاء وتنظيم واشراك المجتمع المدني مؤسساته في اطار ديمقراطي تشاركي من خلال ترسانة من التشريعات والقوانين، ليشكل قوة دافعة للتغيير الاجتماعي والاقتصادي والتنمية المحلية والوطنية من خلال الشراكة في الحياة السياسية، حيث يشارك بفعالية في المبادرات المجتمعية عبر الديمقراطية التشاركية، مما يعزز التعاون بينه وبين الدولة لتحقيق الاستقرار والتقدم والتنمية المحلية في اطار ديمقراطي تشركي من خلال تفعيل دور المجتمع المدني ومحاولة تجاوز مختلف العراقيل والتحديات في سبيل تكريس الديمقراطية التشاركية. ................................ RÉSUMÉ La nécessité d'une société civile efficace, contribuant, aux côtés des institutions étatiques à la realisation du bien public et incarnant la démocratie participative, résulte d'une combinaison de facteurs politiques, économiques et sociaux. Dans les pays développés, les organisations de la société civile jouent un rôle important dans le développement et l'incarnent dans la démocratie participative. Aujourd'hui, elles sont devenues un acteur efficace, aux côtés des pouvoirs publics, pour renforcer le rôle de la société civile dans la fourniture de services que l'État n'a pas assurés. Elles jouent également un rôle essentiel dans le suivi de l'action gouvernementale et la proposition d'alternatives reflétant les besoins et les aspirations des citoyens grâce à la démocratie participative. En Algérie, la société civile s'est développée de manière similaire à celle d'autres pays, notamment au cours des trois dernières décennies, notamment après la promulgation de la Constitution pluraliste de 1989. Celle-ci a instauré une ouverture politique et économique sur le monde en créant, en organisant et en engageant les institutions de la société civile dans un cadre démocratique participatif, fondé sur un ensemble de lois et de textes législatifs. Cette dynamique est devenue un moteur de changement social et économique et de développement local et national, grâce au partenariat dans la vie politique. La société civile participe activement aux initiatives communautaires grâce à la démocratie participative, qui renforce la coopération entre la société civile et l'État pour assurer la stabilité, le progrès et le développement local dans un cadre démocratique participatif. Cet objectif est atteint en activant le rôle de la société civile et en s'efforçant de surmonter les divers obstacles et défis liés à la démocratie participative.
Keywords: Keywords: civil society; participatory democracy; consecrating participatory democracy in Algeria.; الكلمات المفتاحية: المجتمع المدني، الديمقراطية التشاركية، تكريس الديمقراطية التشاركية في الجزائر; Mots-clés : Société civile; démocratie participative; instauration de la démocratie participative en Algérie